EAST INDIA COMPANY AND TRADE IN SOUTH INDIA - Reddy, Moola Atchi. ([S.l.])
1 online resource
Keywords: This book presents the economic history of the English East India Company's trade as it functioned from Madras (Chennai) during the second half of the 18th century. It traces the role of trade and commerce as followed by the European EICs to achieve their economic ends, territorial expansion and control of productive resources. The author portrays the nature, contents, volume and changing trends of trade and commerce over a decisive period of Indian economic history. The volume discusses the chief constituents of trade in general, exports, investments, imports and private trade and traders of Madras from 1746 to 1803. Rich in archival resources, this is an essential resource for administrators, students, scholars and researchers of colonial history and modern Indian economic history, besides British trade history.